I am Kalam [videorecording (DVD)] - Panda, Nilamadhab; Grover, Gulshan; Mayar, Harsh; Saad, Husaan (Ultra Distributors, 2011)
Chotu (Harsh Mayar), a child labourer who works in a roadside dhaba next to an exclusive resort in Rajasthan, nurtures a million dreams. He dreams of wearing a tie someday, going to school and becoming an officer, setting aside his sad destiny of washing dishes, making tea and peeling vegetables. But Chotu isn't a dreamer alone. A chance encounter with President Abdul Kalam, as he delivers a speech on TV, inspires him to fulfil his dreams. He re-christens himself Kalam and finds a priceless friend in young Rannvijay (Husaan Saad), the scion of the princely family that owns the resort.